2019
DOI: 10.1177/1468087419868058
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the soot reduction associated with injection timing variation in a small-bore diesel engine

Abstract: This study shows the in-cylinder soot reduction mechanism associated with injection timing variation in a small-bore optical diesel engine. For the three selected injection timings, three optical-/laser-based imaging diagnostics were performed to show the development of high-temperature reaction and soot within the cylinder, which include OH* chemiluminescence, planar laser–induced fluorescence of hydroxyl and planar laser–induced incandescence. In addition, detailed soot morphology analysis was conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 70 publications
(124 reference statements)
0
4
0
Order By: Relevance
“…On the contrary, when the injection process is delayed, the particle mass concentration decreases. This can be mainly explained because the cylinder temperature remains high during more time along the expansion process, contributing to better oxidation of late-cycle soot, 39 and in a minor extent, because the premixed combustion phase is slightly enhanced at the expense of diffusion combustion.…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, when the injection process is delayed, the particle mass concentration decreases. This can be mainly explained because the cylinder temperature remains high during more time along the expansion process, contributing to better oxidation of late-cycle soot, 39 and in a minor extent, because the premixed combustion phase is slightly enhanced at the expense of diffusion combustion.…”
Section: Resultsmentioning
confidence: 99%
“…400 À Soot in exhaust 30 48À270 À Soot in engine oil 14 45À132 10À35 Soot in engine oil 11 150À500 35À45 Soot in engine oil 29 À 15À50 Soot in engine oil 6 . 400 À Soot inside cylinder 31 273-897 11.65 Soot inside cylinder 32 À 15…”
Section: Type Of Sootmentioning
confidence: 99%
“…Advanced SoI timing exhibited a broader PSD curve than retarded SoI timing (Figure 38). 453 Qu et al 419 reported that the oxidation rate of biodiesel was different from baseline diesel. Diesel droplets exhibited lower surface oxidation than internal oxidation, resulting in lower particulate activation energy.…”
Section: Physical Characterization Of Diesel Soot Particlesmentioning
confidence: 99%